Complex interaction between mutant HNRNPA1 and gE of varicella zoster virus in pathogenesis of multiple sclerosis - Yogita Kattimani; Avinash M. Veerappa (Autoimmunity, 2018)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system causing axonal injury, neuronal loss, and atrophy of the central nervous system leading to permanent neurological and clinical disability. Presence of mutations in M9 domain of HNRNPA1 and detection of autoantibodies against this domain in HNRNPA1 qualifies it as a strong candidate for causing MS. These two aspects indicate the presence of a facilitator in associating them. Varicella zoster virus (VZV), known to cause chicken pox infection in humans, is a significant contender in sensitizing the infected people towards MS. Reactivation of latent herpes viruses by other infectious agents and cross-recognition of common viral antigens with antigens found in the myelin sheath induces molecular mimicry or superantigens. Mutations in HNRNPA1 cause mislocalization to the cytoplasm, and co-localize with stress granules (SG) causing cellular apoptosis, this creates the first step toward MS pathogenesis. Mutant HNRNPA1 accumulates in SG allowing the cells to display peptides of HNRNPA1 on surfaces of major histocompatibility complex (MHC) I triggering a cascade of immune reactions. Since glycoprotein E (gE) of VZV shares >62% amino acids sequence similarity with Prion-like domain (PrLD) of HNRNPA1, signifying the reason behind autoantibodies against M9 and PrLD of HNRNPA1. This review attempts to delineate the interactions of VZV, gE of VZV, with M9 domain and PrLD of HNRNPA1 in a step-by-step process. This supports the tripartite model that an environmental trigger in genetically susceptible individuals causes an autoimmune response to self-CNS antigens that result in the pathology observed in the brain and spinal cord of MS patients.